Design and performance of a high-pressure xenon gas TPC as a prototype for a large-scale neutrinoless double-beta decay search. (26th March 2020) - Ban, S; Hirose, M; Ichikawa, A K; Iwashita, Y; Kikawa, T; Minamino, A; Miuchi, K; Nakadaira, T; Nakajima, Y; Nakamura, K D; Nakamura, K Z; Nakaya, T; et al.
Abstract: A high-pressure xenon gas time projection chamber, with a unique cellular readout structure based on electroluminescence, has been developed for a large-scale neutrinoless double-beta decay search. In order to evaluate the detector performance and validate its design, a 180 L size prototype is being constructed and its commissioning with partial detector has been performed. The obtained energy resolution at 4.0 bar is 1.73 ± 0.07% (FWHM) at 511 keV. The energy resolution at the ^136 Xe neutrinoless double-beta decay Q -value is estimated to be between 0.79 and 1.52% (FWHM) by extrapolation. Reconstructed event topologies show patterns peculiar to the track endpoint that can be used to distinguish 0νββ signals from gamma-ray backgrounds.